Embedding partial 3-star designs - Noble, Matt; Nochumson, Shayne (GTA Research Group, Univ. Newcastle, Indonesian Combinatorics Society and ITB, 2024)
Define a 3-star decomposition of Kn as being a collection of subgraphs, each isomorphic to K1,3, with the property that each edge of Kn appears in exactly one of the subgraphs. A partial 3-star decomposition is similarly defined except each edge appears in at most one of the subgraphs. In this work, it is shown that any partial 3-star decomposition of Kn can be embedded into a decomposition of Kn+s where s ≤ 4. Furthermore, we determine, for any maximal partial 3-star decomposition P of Kn, the minimum s ∈1,2,3,4 such that P can be embedded into a decomposition of Kn+s.